Nutrient Density and Microbial Safety of Open-Air-Dried Beef Meat and Its Biochemical and Organ Histopathology Effects in Albino Rats: A Promising Ingredient for Complementary Food Formulation - Kifle Habte; Meseret Azene; Yohannes Chanyalew; Samson Girma; Chala Bashea; Asrat Yehualshet; Getamesay Behailu; Abiy Abebe; Masresha Tessema (International Journal of Food Science)
Introduction. Dried beef meat is a major source of essential fatty acids, minerals, and vitamins that are digestible and absorbable, thus could be a potential source of nutrients in complementary food formulations. Composition, microbial safety, and organ function tests were analyzed, and histopathological effect of air-dried beef meat powder was determined in rat model. Methods. Three groups of diets were given for the three groups of animals: (1) standard rat diet, (2) meat powder+standard rat diet (1 : 1 formulation), and (3) dried meat powder. A total of 36 Wistar albino rats (18 males and 18 females) of 4-8 weeks old were used and randomly assigned to the experiments. After acclimatization for one week, the experimental rats were followed for 30 days. Microbial analysis, nutrient composition, organ histopathology (liver and kidney), and organ function tests were conducted from serum samples taken from the animals. Results. Protein, fat, fiber, ash, utilizable carbohydrate, and energy contents of meat powder on a dry weight basis were 76.12±3.68, 8.19±2.01, 0.56±0.38, 6.45±1.21, 2.79±0.38 g/100 g, and 389.30±3.25 kcal/100 g, respectively. Meat powder could be also a potential source of minerals such as potassium (766.16±77.26 mg/100 g), phosphorus (150.35±16.26 mg/100 g), calcium (18.15±7.80 mg/100 g), zinc (3.82±0.10 mg/100 g), and sodium (123.76±32.71 mg/100 g). Food intakes were lower in MP group compared to the others. According to organ histopathology results, animals fed with the diet have shown normal values, except rise in alkaline phosphatase (ALP) and creatine kinase (CK) in groups fed with meat powder. The results of organ function tests were all within the acceptable ranges and comparable with their counterpart control groups. However, some of the microbial contents of the meat powder were not within the recommended level. Conclusion. Dried meat powder has a higher amount of nutrients, which would be a potential recipe in complementary food preparation that can support to reduce child malnutrition. However, further studies need to be conducted on the sensory acceptability of formulated complementary foods containing dried meat powder; also, clinical trials are aimed at observing the effect of dried meat powder on child linear growth.